Determinants of Capital Structure: Analysis of the Islamic Banking Industry in the ASEAN Region - Waluyani, Iin; Muflih, Muhammad (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2022)
This study aims to evaluate the factors that influence the capital structure of the Islamic banking industry in the ASEAN region using the trade-off theory as a basis for decision-making. In trade-off theory, book leverage can proxy capital structure as the dependent variable and bank-specific factors, including profitability, earnings volatility, bank size, asset growth, asset structure, and bank age, as independent variables. In addition, it also considers macroeconomic conditions, which are manifested in the gross domestic product and the inflation rate. The study results show that total assets can affect the level of debt because fixed assets can be used as collateral when the bank takes on debt. While other factors do not have a significant effect on the debt level of Islamic banks. These results are the first empirical study to explore the determinants of the capital structure of Islamic banks in the ASEAN region with different variables from previous research and updated sample data, namely the 2016-2020 period.